2019
DOI: 10.1007/s11229-019-02221-w
|View full text |Cite
|
Sign up to set email alerts
|

Error possibility, contextualism, and bias

Abstract: A central theoretical motivation for epistemic contextualism is that it can explain something that invariantism cannot. Specifically, contextualism claims that judgments about "knowledge" are sensitive to the salience of error possibilities and that this is explained by the fact that salience shifts the evidential standard required to truthfully say someone "knows" something when those possibilities are made salient. This paper presents evidence that undermines this theoretical motivation for epistemic context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One representative example involves case judgments in support of leading theories in epistemology. Researchers have shown that subtle confounds in wording and probing in foundational cases can explain judgments about the word "knows" (Turri 2017) and that understanding the mechanisms that cause them can undermine aspects of their theoretical significance (Buckwalter, 2021). In these studies, researchers examined classic pairs of cases used to motivate epistemic contextualism.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…One representative example involves case judgments in support of leading theories in epistemology. Researchers have shown that subtle confounds in wording and probing in foundational cases can explain judgments about the word "knows" (Turri 2017) and that understanding the mechanisms that cause them can undermine aspects of their theoretical significance (Buckwalter, 2021). In these studies, researchers examined classic pairs of cases used to motivate epistemic contextualism.…”
Section: Sample Sizementioning
confidence: 99%
“…As in science, this raises the possibility that judgments about cases are partially explained by previously unaccounted for factors that alter or constrain their theoretical significance. Some research in experimental cognitive science and experimental philosophy suggests that this may be common (Buckwalter, 2021;Chituc et al, 2016;Kneer & Machery, 2019;Rose et al, 2017;Turri, 2017). We often misdiagnose the reasons for judgments or misrepresent their causal structure when utilizing the method of cases.…”
Section: Sample Sizementioning
confidence: 99%
“…For example, the evidence consists of a single experiment utilizing a single measure and narrative case. It is well known that multiple replication attempts involving a wide range of participants, measures, and materials can increase the likelihood that initial discoveries are reliable and generalizable (Open Science Collaboration 2015; see also Buckwalter, 2019;Buckwalter & Turri, 2018;Rose, Buckwalter & Nichols, 2017;Rose, Machery, Stich et at., 2019;Turri, 2017;Turri, 2018;Machery & Doris, 2017). Thus, it is reasonable to investigate this discovery in further detail before drawing strong theoretical conclusions.…”
Section: Introductionmentioning
confidence: 99%